The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.brs.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Timing in the Induction of Neuromodulation in Perceptual Learning by Transcranial Electric Stimulation

Abstract: a b s t r a c tBackground: Transcranial electric stimulation (tES) protocols are able to induce neuromodulation, offering important insights to focus and constrain theories of the relationship between brain and behavior. Previous studies have shown that different types of tES (i.e., direct current stimulation e tDCS, and random noise stimulation e tRNS) induce different facilitatory behavioral effects. However to date is not clear which is the optimal timing to apply tES in relation to the induction of robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 42 publications
9
141
1
1
Order By: Relevance
“…Another study found enhanced effects for online compared with offline stimulation in a picture-naming task for older adults, but not for young adults [montage: anode electrode at left DLPFC, cathode electrode at central zero (Cz) EEG site] (43). Finally, in a visual perceptual learning task, the opposite pattern was found: The effects of offline stimulation were stronger compared with online stimulation (montage: anode electrode at the occipital cortex, cathode electrode positioned extracephalically on the right arm) (44). Therefore, it is possible that the differences between online and offline effects are task-and montage-dependent.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another study found enhanced effects for online compared with offline stimulation in a picture-naming task for older adults, but not for young adults [montage: anode electrode at left DLPFC, cathode electrode at central zero (Cz) EEG site] (43). Finally, in a visual perceptual learning task, the opposite pattern was found: The effects of offline stimulation were stronger compared with online stimulation (montage: anode electrode at the occipital cortex, cathode electrode positioned extracephalically on the right arm) (44). Therefore, it is possible that the differences between online and offline effects are task-and montage-dependent.…”
Section: Discussionmentioning
confidence: 85%
“…The main analysis was based on the full experimental length (40 min, 24 targets and 24 thought probes). Given that the timing of the tDCS stimulation relative to the experimental paradigm might influence the behavioral effects (26,(42)(43)(44), we conducted an additional analysis for the first (online stimulation) and second (offline stimulation) parts of the experiment separately (20 min, 12 targets and 12 thought probes each).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, by using the same PL paradigm (contrast detection) in myopic participants, in a previous study we found that 24 sessions were needed to achieve a VA improvement of 0.16 LogMAR, whereas no improvement in CS was found even with such a long training (Camilleri, Pavan, Ghin, Battaglini, et al, 2014). However, if PL is boosted by the concomitant administration of hf-tRNS as shown by previous studies (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Campana, et al, 2014;Fertonani, et al, 2011;Pirulli, et al, 2013), then 8 sessions of training become enough efficacious to improve uncorrected VA of a similar amount of 24 training sessions with no concurrent stimulation, and to significantly improve uncorrected CS (whereas no improvement was obtained with 24 training sessions using the same paradigm (Camilleri, Pavan, Ghin, Battaglini, et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…The frequencies ranged from 100 to 640Hz (high frequency range). This stimulation protocol has been demonstrated efficacious in boosting perceptual learning in previous studies (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Fertonani, et al, 2011;Pirulli, et al, 2013). The active electrode had an area of 16 cm 2 and was placed over the occipital cortex measured at ~3 cm above the inion.…”
Section: Transcranial Random Noise Stimulation (Trns)mentioning
confidence: 99%
See 1 more Smart Citation